2018
DOI: 10.1007/s40279-018-0963-8
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Metabolic and Vascular Impact of Interrupting Prolonged Sitting: A Systematic Review and Meta-Analysis

Abstract: CRD42015020907.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
151
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 73 publications
17
151
3
6
Order By: Relevance
“…Recently, a meta-analysis [93] reported that activity breaks compared to sitting lowered post-prandial glucose by Cohen [93] for glucose and insulin outcomes were broadly similar to our findings, but with smaller effect sizes. However, we found that PA breaks lowered post-prandial TAG outcomes, in contrast to Saunders et al [93]. The differences in results could be explained by differences in inclusion criteria.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Recently, a meta-analysis [93] reported that activity breaks compared to sitting lowered post-prandial glucose by Cohen [93] for glucose and insulin outcomes were broadly similar to our findings, but with smaller effect sizes. However, we found that PA breaks lowered post-prandial TAG outcomes, in contrast to Saunders et al [93]. The differences in results could be explained by differences in inclusion criteria.…”
Section: Discussionsupporting
confidence: 87%
“…The differences in results could be explained by differences in inclusion criteria. Saunders et al included adolescents and teenagers [94][95][96][97][98] in their meta-analysis [93], whereas we did not. Furthermore, whereas we included studies with people with type 2 diabetes in our meta-analysis, Saunders et al [93] did not.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations